2018
DOI: 10.2472/jsms.67.1020
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar Materials Joining of CFRTP and Aluminum Alloy by Resistance Spot Welding

Abstract: CFRTP (Carbon Fiber Reinforced Thermoplastics) are expected to be used for lightweight component parts in the automobile industry, due to their properties such as high specific strength and high specific stiffness. Because of their expensive cost, however, their application to mass-produced vehicles is limited and expected to be used based on the concept of multi-material combined with conventional materials such as aluminum and steel. For the adaptation of a multi-material body, joining technologies for dissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…There are cracks in the IMC layer, with an uneven distribution of thickness, and the elements are mainly Al and Fe, with the compounds FeAl 3 and Fe2Al 5 , 14–16 and trace Si, Mg, and Ag elements. Zn elements present at the outer edge of the weld core and the compounds produced by Al and Fe have lower metal bonding energy than FeAl 3 and Fe 2 Al 5 , 17–20 so the extrusion of Zn elements is conducive to improving the mechanical properties of welded joints. 2123 Porosity and inclusion defects were present at the weld core, and in situ observation experiments of the liquid aluminum/solid steel reaction revealed that the alumina film ruptured under thermal expansion, phase change expansion, and extrusion of the electrode, and liquid aluminum flowed through the alumina film cracks and contacted with the steel, and then interfacial reactions occurred, which moved the ruptured alumina film upward, an observation that explains the formation of inclusion defects.…”
Section: Sem Analysis Of Welded Joints At Optimum Parametersmentioning
confidence: 99%
“…There are cracks in the IMC layer, with an uneven distribution of thickness, and the elements are mainly Al and Fe, with the compounds FeAl 3 and Fe2Al 5 , 14–16 and trace Si, Mg, and Ag elements. Zn elements present at the outer edge of the weld core and the compounds produced by Al and Fe have lower metal bonding energy than FeAl 3 and Fe 2 Al 5 , 17–20 so the extrusion of Zn elements is conducive to improving the mechanical properties of welded joints. 2123 Porosity and inclusion defects were present at the weld core, and in situ observation experiments of the liquid aluminum/solid steel reaction revealed that the alumina film ruptured under thermal expansion, phase change expansion, and extrusion of the electrode, and liquid aluminum flowed through the alumina film cracks and contacted with the steel, and then interfacial reactions occurred, which moved the ruptured alumina film upward, an observation that explains the formation of inclusion defects.…”
Section: Sem Analysis Of Welded Joints At Optimum Parametersmentioning
confidence: 99%
“…Resistance spot welding, as the main joining method in body construction, has great potential and relevance in realising aluminium/steel joints due to its low cost, high efficiency, high reliability, and ease of automation. [1][2][3][4][5][6] However, the metallurgical incompatibility and the great difference in physical properties between aluminium and steel, as dissimilar metals, pose difficulties in the welding process; additionally, the brittle intermetallic compound layer on the aluminium/steel weld interface degrades the mechanical properties of the joint. [7][8][9][10][11][12] The presence of a zinc layer not only significantly increases the welding current compared to that in bare plate welding of aluminium and steel, [13][14][15] but also leads to inconsistent weld quality and further degrades the mechanical properties of the joint, thus making effective metallurgical joining of zinc-coated steels and aluminium alloys a major challenge in welding processes.…”
Section: Introductionmentioning
confidence: 99%